STRATEGI ADAPTIVE REUSE PADA BANGUNAN CAGAR BUDAYA: STUDI KASUS MUSEUM SABANG - Maharani, Lisa; Fitri, Riza (JMARS: Jurnal Mosaik Arsitektur, 2026)
Adaptive reuse has developed as a conservation approach that bridges the preservation of historic buildings with contemporary functional needs. This study aims to analyze the implementation of adaptive reuse strategies at the Sabang Museum, which previously functioned as the Syahbandar’s official residence during the colonial period. The research employs a qualitative method with a case study approach through field observations, visual documentation, and literature review related to conservation theory and adaptive reuse. The findings indicate that the transformation from a private residence to a public museum was carried out without altering the main structure and architectural character of the building. Interventions were focused on spatial reorganization, visitor circulation adjustments, interior adaptation for exhibition purposes, and the addition of supporting facilities while maintaining visual harmony with the original structure. The study reveals that the adaptive reuse strategy not only preserves the building’s physical value (tangible heritage) but also strengthens its historical and educational significance (intangible heritage) through spatial activation and public activities. Therefore, adaptive reuse can serve as a sustainable conservation strategy for heritage buildings in historic coastal cities.